Rheology of Sesame Pastes with Different Amounts of Water Added - Li-Xia Hou (Journal of Chemistry)
Sesame paste, usually served as a dressing in some local dishes and the desserts in Southeast Asia and the Middle East, requires mixing with water before consumption to form a thin emulsion of the oil-in-water type. Usually water addition is performed empirically and it is difficult to keep the quality of water-mixed sesame paste consistent. In this study, the rheological behavior of sesame paste with different ratios of sesame paste to added water was investigated. The sesame paste tested contains 59.71% of crude fat and 17% of protein. The ratios of sesame paste to added water (w/v) were 1 : 0.75 (T1), 1 : 1 (T2), 1 : 1.25 (T3), and 1 : 1.5 (T4), respectively. All the samples showed the properties of the viscoelastic solids. The samples T1 and T2 behaved as a pseudoplastic material, whereas the apparent viscosity of T3 and T4 remained almost unchanged with the shear rate increasing. T2 had the moderate area of thixotropy loop (57.32 Pa/s) among the tested samples and scored the highest in the sensory evaluation. Therefore, our study suggested that ratio of sesame paste to added water of 1 : 1 (w/v) is suitable for preparing dressings for different dishes.